A Rare and Unusual Case of Burkitt's Lymphoma Presenting with a Prostate Mass in a 12-Year-Old Boy. (13th May 2014) - Sinclair, N.; Babyn, P.; Kinloch, M.; Sinha, R.
Abstract : Burkitt's lymphoma is the most frequent subtype of non-Hodgkin's lymphoma in childhood. Radiographic findings are protean and can often overlap with other neoplastic and nonneoplastic processes. We present an unusual case of Burkitt's lymphoma in a 12-year-old boy presenting with a one-week history of urinary retention, dysuria, and "tailbone pain, " as well as a 4-week history of jaw pain, initially treated as a dental abscess. On dental radiography, the patient was found to have resorption of alveolar bone adjacent to the lower first molars bilaterally, in keeping with "floating teeth, " classically associated with Langerhans cell histiocytosis. Additionally, a large, eccentric, prostatic mass was noted, prompting the inclusion of rhabdomyosarcoma on the differential diagnosis, with subsequent definitive diagnosis of Burkitt's lymphoma on tissue and bone marrow biopsy. This case highlights the imaging overlap of these childhood neoplasms with an unusual lymphomatous prostate mass. It is important that the radiologists and pediatricians be aware of this potential overlap and the unusual presentation of Burkitt's lymphoma.